Relationship between disease awareness and severity of kidney disease in autosomal dominant polycystic kidney disease patients. Issue 1 (10th May 2022) - Dogan, Ege; Eren, Necmi; Ozcan, Seyda Gul; Altunoren, Orcun; Gungor, Ozkan; Dheir, Hamad; Tanrisev, Mehmet; Kocyigit, Hafsa; Yıldız, Abdülmecit; Kocyigit, İsmail and Seyahi, Nurhan and Tatar, Erhan
Abstract: Introduction: Polycystic kidney disease (PKD) is responsible for 5%–10% of end‐stage renal disease. We examined the relationship between renal and extrarenal findings, disease severity, and the level of consciousness of PKD patients. Methods: Patients were asked to answer the questionnaire about PKD. Disease severity was determined according to estimated glomerular filtration rate, and disease awareness was assessed by adapting the Disease Perception Scale to PKD. Awareness of patients was evaluated comparatively with chronic kidney disease stage, age, region, and symptoms. Results: One out of five patients does not know that this disease is inherited. Mean awareness scores of the patients decreased significantly with increasing age. Awareness scores were significantly higher in patients with flank pain, hematuria, and urinary tract stones. Conclusion: Although PKD is the most common hereditary kidney disease, the rate of patients' knowledge on this subject is low. Increased awareness might lead to better treatment in those patients.